2020
DOI: 10.1002/adhm.202001232
|View full text |Cite
|
Sign up to set email alerts
|

Polymers for Melt Electrowriting

Abstract: Melt electrowriting (MEW) is an emerging high‐resolution additive manufacturing technique based on the electrohydrodynamic processing of polymers. MEW is predominantly used to fabricate scaffolds for biomedical applications, where the microscale fiber positioning has substantial implications in its macroscopic mechanical properties. This review gives an update on the increasing number of polymers processed via MEW and different commercial sources of the gold standard poly(ε‐caprolactone) (PCL). A description o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
155
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 151 publications
(172 citation statements)
references
References 137 publications
(290 reference statements)
0
155
0
Order By: Relevance
“…As distance s increases, the electric field strength ( ) decreases accordingly. On average, a voltage of 7 -7.5 kV is reported for MEW-printing of PCL [24]. At a continuous applied voltage of 7.5…”
Section: Resultsmentioning
confidence: 99%
“…As distance s increases, the electric field strength ( ) decreases accordingly. On average, a voltage of 7 -7.5 kV is reported for MEW-printing of PCL [24]. At a continuous applied voltage of 7.5…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical performance of the composite may also depend on the fiber-matrix adhesion and matrix properties which will deserve further investigations. Instability-assisted 3D printing [27,28,45,46], electrospinning [47][48][49] and melt electrowriting [50,51] provide the opportunity for the miniaturization of the microstructured fiber to accommodate different indenter sizes in real-world applications. The transparency of the composite materials can be improved by matching the refractive indexes of the fiber and the elastomer matrix for applications that require high optical transparency [26].…”
Section: Discussionmentioning
confidence: 99%
“…Large sheets of cells could be seen extending or migrating across the scaffold following the trajectory of the supporting walls for several millimeters (Figure 4D,E; white arrows) as well as that of the suspended fibers for distances of ≈1 mm (Figure 4D; black arrows). The cell-cell adhesion between Schwann cells migrating along the suspended PCL fibers, as well as along the supporting walls, resulted in the appearance of whorls of migrating cells, forming (6,12,18, and 24 fiber layers corresponding to 80, 160, 240, and 320 µm respectively), while an additional MEW fiber on the wall (false-colored green) locks the upper suspended fiber into place. B) Suspended fibers intersecting the fiber wall at 45°.…”
Section: Schwann Cell Migration From Explanted Dorsal Root Gangliamentioning
confidence: 99%
“…Detailed reviews on the MEW technology can be found elsewhere. [5,6] To date, MEW scaffolds have been primarily made with a "box-pore" morphology, due to simple programming. On closer inspection for certain scaffold morphologies, there are several instances where suspended fibers spontaneously occur within these scaffolds.…”
Section: Introductionmentioning
confidence: 99%